RISE: Virtual Green Safe Cities Seminar (GRESC 2021) / Dr Siti Rasidah Md Sakip - Md Sakip, Siti Rasidah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
The Green safe Cities (Gresafe) research interest group has successfully organised the Virtual Green Safe Cities Seminar (GreSC 2021) with 'Green Environment For Sustainable Living' as its theme in March 2021 through the YouTube platform.